2015
DOI: 10.1146/annurev-virology-100114-054854
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome Profiling as a Tool to Decipher Viral Complexity

Abstract: Viral genomes harbor a variety of unusual translational phenomena that allow them to pack coding information more densely and evade host restriction mechanisms imposed by the cellular translational apparatus. Annotating translated sequences within these genomes thus poses particular challenges, but identifying the full complement of proteins encoded by a virus is critical for understanding its life cycle and defining the epitopes it presents for immune surveillance. Ribosome profiling is an emerging technique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 88 publications
1
18
0
Order By: Relevance
“…Our current study demonstrates that the two protein isoforms of pUL138 may have both overlapping and distinct functions during HCMV infection. In recent years, many studies have contributed to a body of work that begins to effectively demonstrate the power and function of increased coding capacity in HCMV through transcriptional, translational, and posttranslational mechanisms (9,15,32,33,37,58,59). Further, many examples of viral protein isoforms that have similar or unique functions exist (60)(61)(62)(63)(64)(65)(66)(67), but these examples likely only begin to scratch the surface of the important roles that protein isoforms play in viral infection and virus-host interactions.…”
Section: Identified Cd8mentioning
confidence: 99%
See 1 more Smart Citation
“…Our current study demonstrates that the two protein isoforms of pUL138 may have both overlapping and distinct functions during HCMV infection. In recent years, many studies have contributed to a body of work that begins to effectively demonstrate the power and function of increased coding capacity in HCMV through transcriptional, translational, and posttranslational mechanisms (9,15,32,33,37,58,59). Further, many examples of viral protein isoforms that have similar or unique functions exist (60)(61)(62)(63)(64)(65)(66)(67), but these examples likely only begin to scratch the surface of the important roles that protein isoforms play in viral infection and virus-host interactions.…”
Section: Identified Cd8mentioning
confidence: 99%
“…Estimates of the protein-coding capacity of HCMV have substantially increased with recent studies (32,33) and suggest a complexity in viral protein expression and likely function not previously appreciated. Genomic approaches have also cataloged previously undetected transcribed and translated sequences during both lytic and latent infections (34)(35)(36)(37).…”
mentioning
confidence: 99%
“…Unlike the multitude of viral translation studies reported in the context of infection [102], and likely complicated due to the significant differences between bacterial and eukaryotic translation, to date, no bacterial translatome-oriented studies in the context of infection have been reported.…”
Section: Secretomics For Identifying Bacterial Extracellular Effectormentioning
confidence: 99%
“…Depending on the approach used to arrest ribosomes, the Ribo‐seq technique can capture elongating ribosomes or initiating ribosomes (see Andreev et al., ; Aramayo & Polymenis, ; Bartholomaus, Del Campo, & Ignatova, ; Baudin‐Baillieu, Hatin, Legendre, & Namy, ; Brar & Weissman, ; Calviello & Ohler, ; Gobet & Naef, ; Ingolia, ; Michel & Baranov, ; Mumtaz & Couso, ; Parsons & Myler, ; Stern‐Ginossar, ; Stern‐Ginossar & Ingolia, , for a comprehensive overview of the technique, its applications and limitations). Data tracks for both initiating and elongating ribosomes are hosted on GWIPS‐viz.…”
Section: Introductionmentioning
confidence: 99%